Development of a real-time PCR test system for the identification of Francisella tularensis - Dauletov, A.; Ostrovskii , A.; Tursunbay , N.; Kairzhanova , A.; Mukanov , K.; Amirgazin, A.; Izbanova , U.; Shevtsov , A. (Eurasian Journal of Applied Biotechnology, 2024)
Tularaemia is caused by the Gram-negative bacterium Francisella tularensis, which has three subspecies: holarctica, mediacia and tularensis. Due to the high virulence of the pathogen, the wide range of susceptible animals and the presence of numerous vectors and natural reservoirs, the development of sensitive diagnostic methods for the epidemiological surveillance of tularemia is crucial. New opportunities for understanding the epidemiological situation of tularemia are opening up with the use of new molecular analysis technologies for typing F. tularensis. The development and use of molecular methods for the diagnosis of tularemia is important in this context. The present study developed a protocol for detection of F. tularensis by real-time polymerase chain reaction (qPCR). The selection of primers and a fluorescent probe was based on the aligned sequences of ISFtu1 (multi-copy insertion element). qPCR conditions were optimised, including the determination of the optimal annealing and extension temperatures for the primers. Sensitivity was tested using successive 4-fold dilutions of DNA derived from F. tularensis subsp. mediasiatica, indicating a minimum sensitivity threshold of 15 genomic equivalents per reaction. Two subspecies of F. tularensis (subsp. mediasiatica and subsp. holarctica), 27 non-target bacterial species and 3 eukaryotic organisms were used to assess specificity.